Ecological Toxicity, Oxidative Stress and Impacts of Microplastics on Fish Gills - Waheed, Noman; Naseer, Adeeba; Shabbir, Farwa; Abbas, Muhammad; Iqbal, Saud; Ahmad, Sadeeq; Bashir, Malka Saba; Mahmood, Amina; Rizvi, Syed Muhammad Jawad Raza; Bano, Zahra; Tariq, Bushra (Indus Journal of Bioscience Research, 2025)
Microplastics, which are small plastic particles less than 5 millimeters in size, originate from the degradation of larger plastic items or are intentionally manufactured for various uses. These particles have become ubiquitous in marine and freshwater environments, posing significant risks to aquatic life due to their ability to absorb and concentrate hazardous pollutants. The exposure to Microplastics (MPs), leads to DNA damage in fish that alters the hematological parameters and causes oxidative stress, thereby impacting the overall health of aquatic organisms. MPs also induce an imbalance in reactive oxygen species (ROS) production and antioxidant capacity, causing oxidative damage. In addition, MPs impact immune responses due to physical and chemical toxicity and cause neurotoxicity, altering AchE activity. This review highlights the toxic effects of MPs in fish through various indicators were examined including bioaccumulation, hematological parameters, antioxidant responses, immune responses and neurotoxicity in relation to MP exposure, facilitating the identification of biomarkers of MP toxicity following exposure of fish. This study highlights that the digestive tract contains more microplastics (MPs) than the gills, with fragments, fibers, films, and pellets being the predominant types. FTIR analysis identified polyethylene, polystyrene, polyvinylchloride, polyamide, and polycarbonate in MPs from both gills and the digestive system. MPs pollution triggered oxidative stress responses in gambusia from the East Java Brantas River. While PVC-MPs did not significantly affect gill histopathology or ion regulation, MPs combined with Cu were more toxic than individual pollutants. These findings emphasize the need for further research on the combined effects of MPs and heavy metals on aquatic ecosystems.